What do we know about the future of food systems in West and Central Africa? - Enahoro, Dolapo K.; Mensah, Charles; Gbegbelegbe, Sika (International Food Policy Research Institute, 2025)
Food systems in West and Central Africa (WCA) are challenged by slow growth in productivity and incomes and by climate change.